The impact of economic trends on environmental policy-making (Ökologisches Wirtschaften - Fachzeitschrift, 2015)
In order to explore the relationship between environmental policy-making and economic trends we propose a measurement concept that adopts an aggregate view on the development of policy actions. In a second step, we apply our concept to environmental policy-making and contrast the observed patterns with macroeconomic data.